Evaluating riverine hydrokinetic turbine operations relative to the spatial ecology of wild fishes. Issue 1 (2nd January 2017) - Struthers, Daniel P.; Gutowsky, Lee F.G.; Enders, Eva; Smokorowski, Karen; Watkinson, Doug; Bibeau, Eric; Cooke, Steven J.
ABSTRACT: Hydrokinetic turbines (HTs) are being proposed for placement in riverine landscapes around the globe. Here, we implanted 40 adult lake sturgeon and 40 adult walleye with acoustic telemetry transmitters to monitor their lateral and vertical space use at the Canadian Hydrokinetic Turbine Testing Centre (CHTTC) located in the Seven Sisters Generating station (GS) tailrace on the Winnipeg River, Manitoba. Specifically, we tested whether fish behaviour was influenced by the operation of HTs relative to control periods, and estimate the threat of HTs towards lake sturgeon and walleye across seasons. The behaviour and habitat use of both species was not influenced by HT operations. Greater numbers of walleye were present when the discharge rate was ≥ 950 m 3 s –1, which is ≥ 77 m 3 s –1 greater than the average discharge rate (873 m 3 s –1 ) measured during the study period. Given the patterns of seasonal residency, movement, and depth use, lake sturgeon appeared more prone to interacting with HTs during spring and early summer months (i.e. May and June), whereas risk to walleye would be highest throughout the summer and autumn months. In the vicinity of the acoustic receivers, available habitat (areas with large boulders, and transitions between swift flow in the channel and slacker water near the shoreline) was used significantly more often by walleye than lake sturgeon. Lake sturgeon utilized similar depths where HTs would be installed (i.e. ≥ 6.5 m), while walleye commonly occupied shallower depths at the HT testing centre making the former more susceptible to interactions with substrate-HT's. Collectively, these are some of the first field-based results on fish behaviour and ecology while a riverine-HT is in operation. The findings present useful information to help guide best practices for commercial scale HT operations within river systems where lake sturgeon and walleye reside.